ANALISIS PENGARUH MOTIVASI KERJA, PENGEMBANGAN KARIR DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA KARYAWAN (Studi Pada Karyawan Bagian Produksi PT Temprina Media Grafika Jawa Pos Group Cabang Semarang) - Wiyani, Ersani Adhitya; Rahardjo, Mudji (Faculty of Economics and Business Diponegoro University, 2015)
Development of a printing industry ynot only promote the quality, timeliness and quality and quantity as requested, but also requires the management of human resource is appropriate. This study aims to explain how the variables influence of work motivation, career development and organizational commitment to the employee performance on PT Temprina Media Grafika Semarang.The population used in this study were all employees of PT Temprina Media Grafika Semarang numbering 65 people. The sampling technique was conducted by the method of jenuh sampling. The analytical method used is multiple regression analysis. The results of a study reported regression equation as follows: Employee Performance = 0,200X1 + 0,366X2 + 0,671X3Based on the test instrument, the indicators are valid and reliable. In the classical assumption, there are no symptoms multicoloniarity, does not occur heterocedastity, and normal distribution of data. The coefficient of determination shows the figure of 0.741 which means that the variables of employee performance is influenced by variables of work motivation, career development and organisational commitment amounting to 74.1 %. The results showed that work motivation, career development and organisational commitment positive and significant impact employees performance of PT Temprina Media Grafika Semarang either partially or simultaneously.